Silvicultural performance of eucaliptus and animal behavior in a silvopastoral system (Bioscience Journal, 2019)
Silvopastoral system, in which trees and forage species are grown in the same area together with animals, has emerged as a sustainable alternative of agricultural production systems. However, information on different silvicultural arrangements and combinations of forest, animal and grazing components in this system are still scarce. Thus, this study followed the silvicultural performance of the forest component (Eucalyptus urophylla x E. grandis, eucalyptus hybrid, clone I-144) under different population arrangements in a silvopastoral system through periodic dendrometric evaluations and determined the impact of animal component (Nellore females) on tree development and ingestive behavior of animals subjected to rotational grazing in Urochloa brizantha cv. Marandu. The study was conducted at Agropecuária Ouro Branco, located in Bandeirantes, MS, Brazil. Total height, diameter at breast height, and wood volume per hectare were evaluated in three- and five-row ranks. To indicate plant growth, the current and average annual increments were calculated. Animal behavior was evaluated based on the periodic observation of 15 animals randomly selected in the lot. The initial performance of forest component was satisfactory in both populations, but growth indicators indicated greater current and average annual increments in the five-row rank. The presence of forest component does not interfere with the ingestive behavior and wellbeing of animals in the silvopastoral system, as well as, the presence of animal component does not interfere in the plants silvicultural development.